Overcoming the immune suppressive nature of glioblastoma by leveraging the surgical intervention - current status and future perspectives - Duerinck, Johnny; Tuyaerts, Sandra; Movahedi, Kiavash; Neyns, Bart (Frontiers in Immunology, 2023)
Despite relentless efforts to improve outcome, the prognosis of glioblastoma (GBM) remains poor. Standard therapy at first diagnosis consists of maximal safe surgical resection followed by radiochemotherapy, but treatment options at recurrence are scarce and have limited efficacy. Immunotherapy is a broad term that covers several treatment strategies, including immune checkpoint inhibition (ICI). The successes of systemically administered therapeutic monoclonal antibodies that block the Programmed death receptor or ligand-1 (PD-(L)1) and Cytotoxic T-Lymphocyte associated protein-4 (CTLA-4) immune checkpoints in other cancer types could not be reproduced in glioblastoma. This is considered to be related to the intrinsic low immunogenicity and strong immunosuppressive tumor microenvironment of glioblastoma, in addition to the presence of a blood-glioma and blood-brain barrier that limits many systemically administered therapeutic agents from reaching their target. In this mini-review, we address the specific aspects of immune suppression in glioblastoma and discuss potential strategies that could help to overcome it. The potential advantages of incorporating surgical resection in clinical trials of immunotherapy for glioblastoma, including window-of-opportunity studies, are highlighted. Combination strategies that include surgical resection, as well as local administration of therapeutic agents in the brain are discussed as a potential strategy to achieve an effective immunological response against glioblastoma.